2013
DOI: 10.3389/fncom.2013.00111
|View full text |Cite
|
Sign up to set email alerts
|

Learning to never forget—time scales and specificity of long-term memory of a motor skill

Abstract: Despite anecdotal reports that humans retain acquired motor skills for many years, if not a lifetime, long-term memory of motor skills has received little attention. While numerous neuroimaging studies showed practice-induced cortical plasticity, the behavioral correlates, what is retained and also what is forgotten, are little understood. This longitudinal case study on four subjects presents detailed kinematic analyses of humans practicing a bimanual polyrhythmic task over 2 months with retention tests after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 70 publications
(86 reference statements)
5
30
0
Order By: Relevance
“…These results are consistent with previous findings by Park et al (2013) who reported retention of spatiotemporal patterns not only after 6 mo, but also after 8 yr. However, due to the longitudinal nature of this previous experiment, results from only four subjects were reported with two cases for the 8-yr retention.…”
Section: Hypothesis 2: Robust Retention Of Spatiotemporal Patternssupporting
confidence: 96%
See 4 more Smart Citations
“…These results are consistent with previous findings by Park et al (2013) who reported retention of spatiotemporal patterns not only after 6 mo, but also after 8 yr. However, due to the longitudinal nature of this previous experiment, results from only four subjects were reported with two cases for the 8-yr retention.…”
Section: Hypothesis 2: Robust Retention Of Spatiotemporal Patternssupporting
confidence: 96%
“…This result corroborates the previous case study, where subjects acquired a 3:1 pattern without any feedback (Park et al 2013). This previous experiment also highlighted the presence of several time scales in different variables, which was again seen in the present study.…”
Section: Hypothesis 1: Self-guided Learning With and Without Metronomesupporting
confidence: 95%
See 3 more Smart Citations